Cesium extraction composite material as well as preparation method and application thereof
By preparing cesium titanate composite materials, using tetrabutyl titanate and nano-silica and other materials, the existing cesium extraction method has complex processes, large energy consumption and short service life of adsorbents, and an efficient and environmentally friendly cesium ion adsorption effect has been achieved.
Patent Information
- Application Number
- CN202411791319.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-21
AI Technical Summary
The existing methods for cesium extraction have complex processes, large energy consumption, and have a great impact on the environment. The adsorbent has low mechanical strength, poor hydraulic performance, and short service life, making it difficult to meet the needs of industrial applications.
Solution A is prepared by mixing tetrabutyl titanate with anhydrous ethanol, and then reacting cesium acetate with oxalic acid and added to solution A to form a precursor solution of cesium titanate, and then nanosilicon dioxide is added. After sonication, stirring in a water bath and drying, the composite material is finally roasted in a muffle furnace.
The exchange rate and adsorption capacity of the adsorbent are improved, and the problem of slow adsorption rate caused by dense layered structures is solved. The adsorption capacity can reach more than 329 mg/g, and the adsorbent can be recycled and recycled and has a long life.
Smart Images

Figure CN119657072A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a cesium extraction composite material and a preparation method and application thereof. Background Art
[0002] As an important strategic resource, alkali metal cesium and its compounds have good ductility, excellent electrical and thermal conductivity, and excellent photoelectric effect performance. They are widely used in high-tech fields such as perovskite solar cells, catalysis, atomic clocks, communications, and medical tracing. It can be used in infrared radiation sources, atomic clocks, magnetohydrodynamic generators, thermionic power generation, ion engines, hollow cathode lamps, photomultiplier tubes, camera tubes, micro batteries, scintillation counters, lasers, special glass, sedatives, catalysts, etc. In recent years, with the development of science and technology, the demand for cesium and its compounds has increased day by day.
[0003] my country's cesium resources mainly exist in ores and salt lake brine. The process of extracting cesium from ores is relatively mature, mainly sulfuric acid leaching and roasting-water leaching. This method still has problems such as complex process flow and high energy consumption. In addition, a large amount of tail gas emissions will have a certain impact on the environment, which is not in line with the concept of green industry and has a great impact on achieving my country's "dual carbon" goals. Solvent extraction and ion exchange are generally used to extract cesium from salt lake brine. These methods have the advantages of simple process flow, strong continuity, low energy consumption, and low emissions, and have broader development prospects.
[0004] At present, the main methods for extracting cesium include fractional crystallization, precipitation, solvent extraction and adsorption. The adsorption method is suitable for the separation and enrichment of low-concentration cesium. It has a simple process and is environmentally friendly. It is a separation method with great industrial application prospects.
[0005] CN102266745A discloses a method for preparing a magnetic cesium selective adsorbent, wherein Ni(NO 3 ) 2 Slowly add K 4 Fe(CN) 6 -CH 3 COOH solution, after the solution is added dropwise, the reaction continues for a period of time, after the reaction is completed, the solution is allowed to settle, the supernatant is decanted, and then filtered, washed, and dried at 110°C to prepare a nickel potassium ferrocyanide adsorbent. The adsorbent is a pure inorganic material, has high selectivity for Cs and fast exchange rate, but the adsorbent composed of pure nickel potassium ferrocyanide has low mechanical strength, poor hydraulic properties, short service life, and is not conducive to industrial application.
[0006] CN103736472B discloses a gel-type cesium ion adsorbent, which is a rubidium tungstate silicotungstate-calcium alginate gel-type microsphere, which has a high cesium ion adsorption capacity and good selectivity. However, the gel microspheres usually shrink greatly in volume when drying and are easily broken, which limits their practical application.
[0007] CN109967048A discloses a resin-based nanocomposite adsorbent for extracting cesium from brine and a preparation method thereof. An in-situ polymerization method is used to synthesize a porous resin doped with an inorganic nano-silicon material, and then potassium cobalt ferrocyanide is loaded into the porous resin doped with the inorganic nano-silicon material by a vacuum impregnation method to prepare a resin-based nanocomposite adsorbent. The adsorbent utilizes the high specific surface area of the inorganic nano-silicon material to increase the loading amount of the porous resin for potassium cobalt ferrocyanide, thereby increasing the adsorption capacity of the adsorbent. However, under alkaline conditions, the active component nano-cobalt potassium cyanide particles in the adsorbent are easily deactivated, and the resin-based structure is easily destroyed, resulting in reduced adsorption effect, decreased adsorption rate, and a short life of the adsorbent.
[0008] CN116688949A discloses a metal-doped organic amine tin sulfide adsorbent, a preparation method and an application for cesium extraction. An organic amine solution, tin powder, sulfur powder and doped metal or its oxide powder are placed in a reactor with a polytetrafluoroethylene liner, and a solvent is added and stirred evenly; the mixture is placed in a reactor, heated to 160-200°C in a vacuum drying oven, and reacted at a constant temperature for 48-72 hours under this condition, and then cooled to room temperature to obtain a reaction product; the product is washed and dried to obtain a metal-doped organic amine tin sulfide adsorbent. It effectively solves the problem of low adsorption capacity and slow adsorption rate of traditional cesium ion adsorbents such as heteropolyacid adsorbents and Prussian blue adsorbents, but organic amine tin sulfide is prone to failure under alkaline conditions, resulting in reduced adsorption efficiency, reduced adsorption rate and short adsorption life. Summary of the invention
[0009] The main purpose of the present invention is to provide a method for preparing a cesium-extracting composite material, aiming to solve the above technical problems.
[0010] To achieve the above object, the present invention provides a method for preparing a cesium-extracting composite material, comprising:
[0011] Tetrabutyl titanate and anhydrous ethanol are mixed and stirred uniformly to prepare solution A;
[0012] After dissolving cesium acetate, add oxalic acid and heat and stir to obtain solution B;
[0013] Solution B is slowly added to solution A at a certain flow rate, stirred evenly to obtain a cesium titanate precursor solution, and concentrated hydrochloric acid is added to adjust the pH for acid modification;
[0014] Slowly adding nano-silicon dioxide into the precursor solution according to a certain loading amount;
[0015] The mixed solution was subjected to ultrasonic treatment, stirred in a water bath and then placed in an oven to dry;
[0016] The dried product is placed in a muffle furnace and calcined to obtain a composite material.
[0017] In one embodiment, the preparation of the nano-silicon dioxide comprises:
[0018] Take ethyl orthosilicate as silicon source, control the volume ratio of water and ethanol between 1:2-1:5, the volume of dilute hydrochloric acid is 1%-6% of the total volume of the mixed solution, stir at 200-400rpm for 1-2 hours to form nano silica sol.
[0019] In one embodiment, the step of slowly adding nano-silicon dioxide into the precursor solution at a certain loading amount is specifically as follows:
[0020] The nano-silicon dioxide is slowly added into the precursor solution at a loading amount of 20%-70%.
[0021] In one embodiment, the silica sol is added to the cesium titanate precursor solution at a flow rate of 1-3 drops / second, and then ultrasonicated, stirred, dried, and calcined.
[0022] In one embodiment, the steps of ultrasonically treating the mixed solution, stirring in a water bath and then drying in an oven are specifically as follows:
[0023] The mixed solution was ultrasonically treated for 30-60 minutes, stirred in a water bath at 50-80°C for 90-180 minutes, and then dried at 80-120°C for 12-24 hours.
[0024] In one embodiment, the step of placing the dried product into a muffle furnace and calcining it to obtain a composite material is specifically as follows:
[0025] Calcinate at 400-600℃ for 2-6 hours and then grind.
[0026] In addition, the present invention also provides a cesium extraction composite material, which is prepared by the preparation method of the cesium extraction composite material as described above.
[0027] In addition, the present invention also provides an application of a cesium extraction composite material, characterized in that the cesium extraction composite material is applied to extract cesium from liquid cesium ore.
[0028] In the technical solution of the present invention, tetrabutyl titanate is used as a source of titanic acid, which needs to be protonated in the reaction to change the spatial structure and charge distribution, so as to achieve the adaptation to the size and charge distribution of cesium ions and improve the adsorption amount. Loading nano-silicon dioxide can increase the pores and solve the influence of the slow adsorption rate caused by the dense layered structure. When this adsorbent is used to extract the dispersed element cesium in liquid resources, it has the advantages of fast exchange rate and large adsorption capacity. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.
[0030] Figure 1 The figure is a schematic flow chart of a method for preparing a cesium-extracting composite material according to an embodiment of the present invention.
[0031] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] It should be noted that all directional indications in the embodiments of the present invention (such as up, down, left, right, front, back, etc.) are only used to explain the relative position relationship, movement status, etc. between the components under a certain specific posture (as shown in the accompanying drawings). If the specific posture changes, the directional indication will also change accordingly.
[0034] In addition, in the present invention, descriptions such as "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" or "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0035] Furthermore, the technical solutions between the various embodiments of the present invention may be combined with each other, but this must be based on the fact that they can be implemented by ordinary technicians in the field. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such combination of technical solutions does not exist and is not within the scope of protection required by the present invention.
[0036] The invention provides a cesium extraction composite material and a preparation method thereof.
[0037] like Figure 1 As shown, the preparation method of the cesium extraction composite material provided by the embodiment of the present invention includes:
[0038] (1) Tetrabutyl titanate and anhydrous ethanol are mixed and stirred to prepare a solution A;
[0039] (2) dissolving cesium acetate, adding oxalic acid, and heating and stirring to obtain solution B;
[0040] (3) slowly adding solution B to solution A at a certain flow rate, stirring evenly to obtain a cesium titanate precursor solution, and adding concentrated hydrochloric acid to adjust the pH for acid modification;
[0041] (4) slowly adding nano-silicon dioxide into the precursor solution at a certain loading amount;
[0042] (5) subjecting the mixed solution to ultrasonic treatment, stirring in a water bath, and then drying in an oven;
[0043] (6) The dried product is placed in a muffle furnace and calcined to obtain a composite material.
[0044] In step (1), tetrabutyl titanate and anhydrous ethanol undergo a hydrolysis reaction, and the reaction equation is: Ti(OC 4 H 9 ) 4 +xH 2 O→Ti(OH) x (OC 4 H 9 ) 4-x +xC 4 H 9 OH.
[0045] In step (1), solution A contains a hydroxyl titanate intermediate and butanol.
[0046] The hydroxyl groups generated by the hydrolysis reaction in step (1) undergo a polycondensation reaction, causing the molecules to gradually cross-link to form a gel with a three-dimensional network structure. The dehydration polycondensation reaction equation is: M-OH+HO-M→MO-M+H 2 O (M is a partial structure containing titanium).
[0047] Preferably, in step (2), cesium acetate is ionized into oxalate and cesium ions in the solution, and oxalic acid is added to accelerate the acid-base neutralization reaction between hydrogen ions and acetate ions to generate acetic acid (CH 3 COOH).
[0048] Preferably, the cesium ions ionized in step (3) interact with the titanium compound in the gel and participate in the formation of the gel structure to generate a cesium titanate precursor solution. However, the specific reaction process is relatively complicated. The reaction equation when liquid B is added to liquid A is 6Ti(OH) x (OC4H9) 4-x +2Cs + →Cs 2 Ti 6 O 13 +…….
[0049] Preferably, in step (4), ethyl orthosilicate is used as the silicon source, and the volume ratio of ethyl orthosilicate to water and ethanol is controlled between 1:2-1:5, the volume of dilute hydrochloric acid is about 1%-6% of the total volume of the mixed solution, and the mixture is stirred at a speed of 200-400 rpm for 1-2 hours to form a silica sol.
[0050] Preferably, the loading amount in step (4) is 20%-70%.
[0051] Preferably, in step (4), the silica sol is added to the cesium titanate precursor solution at a flow rate of 1-3 drops / second, and ultrasonication, stirring, drying and calcination are performed.
[0052] Preferably, in step (5), ultrasonication is performed for 30-60 minutes, stirring is performed at 50-80° C. for 90-180 minutes, and baking is performed at 80-120° C. for 12-24 hours.
[0053] Preferably, in step (6), the powder is ground after being calcined at 400-600° C. for 2-6 hours.
[0054] According to a second aspect of the present invention, there is also provided an application of the above-mentioned cesium extraction composite material to extract cesium from liquid cesium ore.
[0055] Specifically, the cesium extraction composite material is placed in leaching brine containing a cesium ion concentration of 40-100 mg / g, and the exchange is carried out for no less than 60 minutes, and a solid sample rich in cesium is obtained by filtration.
[0056] Furthermore, after the cesium element is adsorbed in the ion exchanger, it can be regenerated using an eluent.
[0057] The invention provides a preparation method of a cesium-extracting composite material and its application in cesium-extracting. In the reaction, tetrabutyl titanate is used as a source of titanic acid, and it needs to be protonated in the reaction to change the spatial structure and charge distribution, so as to achieve the adaptation with the size and charge distribution of cesium ions and improve the adsorption amount. Loading nano-silicon dioxide can increase the pores and solve the influence of the slow adsorption rate caused by the dense layered structure. When the adsorbent is used to extract the scattered element cesium in liquid resources, it has the advantages of fast exchange rate and large adsorption capacity, and the adsorption capacity can reach more than 329 mg / g, and it can be recycled and reused, the adsorbent has a long service life, and the process operation is simple, which is of great significance for the efficient enrichment and recovery of cesium ions in solid cesium ore or associated ore leachate and geothermal water, salt lake brine, and underground brine.
[0058] The present invention is further described in detail below with reference to specific embodiments.
[0059] Example 1
[0060] A certain amount of tetrabutyl titanate, such as 10 mL, is slowly added dropwise to an appropriate amount of anhydrous ethanol, 50 mL, and stirred evenly. A small amount of concentrated hydrochloric acid is added to adjust the pH value of the solution to 2, thereby preparing solution A.
[0061] Dissolve 11.3 g of cesium acetate in 100 ml of water, add 18.8 g of oxalic acid, and stir for 60 minutes in a constant temperature water bath at 60°C to obtain a clear and transparent solution B. Slowly drop solution B into solution A, control the drop rate at 1 mL / min, and continue stirring. After the drop addition is completed, continue to stir the reaction system and react for 2 hours to obtain a cesium titanate precursor solution.
[0062] Take 4.1 g of tetraethyl orthosilicate at a loading amount of 10% and slowly add it dropwise to a mixed solution containing an appropriate amount of anhydrous ethanol, deionized water and dilute hydrochloric acid (the volume ratio of tetraethyl orthosilicate to water and ethanol is 1:2, and the volume of dilute hydrochloric acid is about 2% of the total volume of the mixed solution) and stir for 90 minutes to obtain silica sol.
[0063] The silica sol was slowly added to the cesium titanate precursor solution, and after ultrasonic treatment for 60 minutes, it was stirred in a 70°C water bath for 90 minutes, and then transferred to an oven and baked at 90°C for 2 hours. After grinding, it was placed in a muffle furnace and calcined at 400°C for 2 hours, and then ground to obtain a powdered composite adsorption material.
[0064] 100 ml of leaching brine was put into a conical flask, and the cesium content was determined to be 60.0 mg / g. 1 g of the composite adsorbent material was put into the brine and shaken at 40°C for 60 minutes. After the adsorption was completed, the solution and the adsorbent material were transferred to a centrifuge tube and centrifuged for 10 minutes. The supernatant was taken and the cesium content was determined to be 5.4 mg / g, and the adsorption rate was 91%. The adsorbent material after centrifugation was eluted with 0.2 M hydrochloric acid.
[0065] Example 2
[0066] The preparation process of cesium titanate precursor solution is the same as that of Example 1, except that 24.6 g of ethyl orthosilicate is used to prepare silica sol at a loading amount of 40%, and the loading process is the same as that of Example 1. 100 ml of leached brine is put into a conical flask, and the cesium content is determined to be 83.0 mg / g. 1 g of composite adsorbent material is put into the brine and shaken at 40° C. for 60 minutes. After the adsorption is completed, the solution and adsorbent material are transferred to a centrifuge tube and centrifuged for 10 minutes. The supernatant is taken and the cesium content is determined to be 1.66 mg / g, and the adsorption rate is 98%. The adsorbent material after centrifugation is eluted with 0.2 M hydrochloric acid.
[0067] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification and drawings under the concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.
Claims
1. A method for preparing a cesium-extracting composite material, characterized in that: The preparation method of the cesium extraction composite material comprises: Tetrabutyl titanate and anhydrous ethanol are mixed and stirred uniformly to prepare solution A; After dissolving cesium acetate, add oxalic acid and heat and stir to obtain solution B; Solution B is slowly added to solution A at a certain flow rate, stirred evenly to obtain a cesium titanate precursor solution, and concentrated hydrochloric acid is added to adjust the pH for acid modification; Slowly adding nano-silicon dioxide into the precursor solution according to a certain loading amount; The mixed solution was subjected to ultrasonic treatment, stirred in a water bath and then placed in an oven to dry; The dried product is placed in a muffle furnace and calcined to obtain a composite material.
2. The method for preparing the cesium-extracting composite material according to claim 1, characterized in that: The preparation of the nano silicon dioxide comprises: Take ethyl orthosilicate as silicon source, control the volume ratio of water and ethanol between 1:2-1:5, the volume of dilute hydrochloric acid is 1%-6% of the total volume of the mixed solution, stir at 200-400rpm for 1-2 hours to form nano silica sol.
3. The method for preparing the cesium-extracting composite material according to claim 2, characterized in that: The step of slowly adding nano-silicon dioxide into the precursor solution at a certain loading amount is specifically as follows: The nano-silicon dioxide is slowly added into the precursor solution at a loading amount of 20%-70%.
4. The method for preparing the cesium-extracting composite material according to claim 1, characterized in that: The silicon dioxide sol is added dropwise to the cesium titanate precursor solution at a flow rate of 1-3 drops / second, and then ultrasonicated, stirred, dried and calcined.
5. The method for preparing the cesium-extracting composite material according to claim 1, characterized in that: The steps of ultrasonically treating the mixed solution, stirring in a water bath and then drying in an oven are specifically as follows: The mixed solution was ultrasonically treated for 30-60 minutes, stirred in a water bath at 50-80°C for 90-180 minutes, and then dried at 80-120°C for 12-24 hours.
6. The method for preparing the cesium-extracting composite material according to claim 1, characterized in that: The step of placing the dried product into a muffle furnace for calcination to obtain a composite material is specifically as follows: Calcinate at 400-600℃ for 2-6 hours and then grind.
7. A cesium extraction composite material, characterized in that: The cesium extraction composite material is prepared by the preparation method of the cesium extraction composite material according to any one of claims 1 to 6.
8. An application of a cesium extraction composite material, characterized in that: The cesium extraction composite material is applied to extract cesium from liquid cesium ore.
Citation Information
Patent Citations
A method for preparing an inorganic cesium selective adsorbent
CN102266745A
Gel spherical cesium ion adsorbent, its preparation method and application
CN103736472B
Resin-based nano composite adsorbent used for extracting cesium from brine and preparation method of adsorbent
CN109967048A
Metal-doped organic amine tin sulfide adsorbent, preparation method and cesium extraction application
CN116688949A